Analisis Keandalan Jaringan Distribusi 20 kV di UP3 Surakarta Menggunakan Metode Section Technique Berbasis Optimal Placement Recloser - Ridwan , Azdreine Azzizah; Fadlilah, Umi (Jurnal Ragam Pengabdian, 2026)
This study evaluates the reliability of the 20 kV distribution network at PT PLN (Persero) UP3 Surakarta, focusing on the JJR-03 feeder. Using the Section Technique method, the network was divided into sections to calculate failure rates, disruption duration, and reliability indices (SAIFI and SAIDI) based on disruption data, customer numbers, line length, and network components. The results show that the JJR-03 feeder has a SAIFI of 5.538 times/year and a SAIDI of 20.930 hours/year, with Section 1 contributing the largest disruptions due to its longer line length, more components, and higher customer density. ETAP 19.0.1 simulations revealed initial SAIFI and SAIDI values of 7.766 times/year and 21.341 hours/year. After optimizing recloser placement in the highest-disturbance section, SAIFI decreased to 5.821 times/year and SAIDI to 16.164 hours/year. These findings indicate that strategic recloser placement can significantly improve distribution system efficiency by reducing outage frequency and duration. The study provides a basis for developing more effective protection system strategies to enhance the reliability of the 20 kV distribution network on the JJR-03 feeder.